An Exploratory Interview Study on Travel Risk Perception: The Case of Phuket Sandbox - FUCHS, Kevin (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).14, 2022)
Travel risk perception is a factor with emerging importance in the tourism industry due to its intangible nature, but large impact on traveler’s decision-making. This exploratory study examines the perception of travel risk amid COVID-19 in the New Normal. The empirical data was gathered through a series of thirty-eight (38) semi-structured interviews with European visitors vacationing in the 'Phuket Sandbox' travel bubble. The thematic analysis based on the empirical data revealed four themes. Namely, these themes are (1) the status of COVID-19 in the destination country, (2) visibility and trustworthiness of information, (3) healthcare facilities, and (4) responsible tourism development. The article concludes by presenting implications for the industry, policymakers, and researchers derived from the academic and practical discussions based on the findings.